(untitled) (Eureka Journal of Agricultural Science & Bio-Innovation, 2026)
This study evaluated the insecticidal activity of the Bacillus thuringiensis B12 strain against agricultural insect pests under laboratory conditions. The investigation was aimed at determining the efficacy of the bacterial strain in suppressing pest populations through concentration-dependent bioassays. Selected pest insects were exposed to different concentrations of the B12 strain, and mortality rates were recorded over a defined observation period. The findings demonstrated that the Bacillus thuringiensis B12 strain exhibited significant insecticidal activity compared with the control treatment. A clear increase in insect mortality was observed as the concentration of the bacterial preparation increased, indicating a strong dose-response relationship. The results confirmed that the strain was biologically active and capable of affecting pest survival under controlled experimental conditions. The observed pattern of mortality suggests that the B12 strain possesses considerable potential for integration into environmentally safer pest management strategies. As a microbial control agent, Bacillus thuringiensis offers an alternative to chemical insecticides by reducing ecological risks and supporting sustainable agricultural production. The present findings therefore highlight the practical importance of the B12 strain as a promising biological control agent for managing agricultural insect pests and provide a scientific basis for further applied and field-based investigations.